Analisis Kapasitas Perguruan Tinggi dalam Mendukung Implementasi Sertifikasi Halal: Studi Kasus Halal Center UIN Madura - Z.A, Khayrus Sabiqin; Fahrurrozi; Muhtadi, Ridan (Kartika: Jurnal Studi Keislaman, 2025)
Universities, through halal centers, participate in supporting the implementation of halal certification. The halal center assists BPJPH in fulfilling halal obligations by providing halal assistance to MSME actors to obtain halal certification. The existence of the Halal Center plays an important role for business actors in the implementation of halal certification. However, there are several challenges, such as a lack of understanding among MSME actors regarding halal certification obligations and a lack of support from local governments and university institutions, which hinder its implementation. In this study, a qualitative descriptive method was used as a technique for data collection through interviews, observations, and documentation of the leadership of the UIN Madura Halal Center. This study aims to identify and determine the extent to which the UIN Madura Halal Center is capable of supporting the implementation of halal certification using several indicators, such as institutional, operational, collaborative, and socio-economic impacts. The results of this study indicate that the UIN Madura Halal Center is capable of supporting the implementation of halal certification for MSMEs. However, in its implementation, there are still problems such as a lack of financial support in building the LPH halal laboratory and a lack of halal assistants.